Central nervous system (CNS) medications and polypharmacy in later life: cross-sectional analysis of the English Longitudinal Study of Ageing (ELSA). Issue 9 (14th September 2020) - Slater, Natasha; White, Simon; Frisher, Martin
Abstract : Objectives: Many central nervous system (CNS) medications are considered potentially inappropriate for prescribing in older people; however, these medications are common in polypharmacy (≥5 medicines) regimens. This paper aims to determine the prevalence of CNS drug classes commonly taken by older people. Furthermore, this paper aims to determine whether polypharmacy and other factors, previously found to be associated with overall polypharmacy, are associated with the most common CNS drug classes. Design: Cross-sectional study. Setting: English Longitudinal Study of Ageing (wave 6). Participants: 7730 participants (≥50 years). Main outcome measures: Adjusted Odds Ratios (OR) and 95% confidence intervals (CI) for CNS drug classes. Results: 31% of the sample were currently taking ≥5 medications (polypharmacy), of whom 58% (n=1362/2356) were taking CNS medicines as part of their regimen. The most common CNS drug classes in polypharmacy regimens were non-opioid analgesics, opioid analgesics, tricyclic and related antidepressants (TCAs) and selective serotonin reuptake inhibitors (SSRIs) (34.6%, 13.2%, 10.9% and 10.4%, respectively). Compared with people currently taking 1–4 prescribed medicines, polypharmacy was associated with adjusted ORs of 5.71 (95% CI: 4.29 to 7.61, p<0.01) for opioid analgesics, 3.80 (95% CI: 3.25 to 4.44, p<0.01) for non-opioid analgesics, 3.11 (95% CI: 2.43 to 3.98, p<0.01) for TCAs and 2.30 (95% CI: 1.83 to 2.89, p<0.01) for SSRIs. Lower wealth was also associated with the aforementioned CNS drug classes. Conclusion: Opioid and non-opioid analgesics were the most prevalent classes of CNS medicines in this study. Polypharmacy is strongly associated with the aforementioned classes of analgesics. Polypharmacy is also associated with TCAs and SSRIs, although to a lesser extent than for analgesics. For all CNS medicine classes, polypharmacy may need to be considered in relation to reducing the risk of potential adverse events. After adjustment, lower wealth is associated particularly with analgesics, highlighting that socioeconomic factors may play a role in the prescribing of CNS medicines. These findings provide a baseline for future research into this area.